Hydrophobic organic coating based water--solid TENG for water-flow energy collection and self-powered cathodic protection - LIU, Yupeng; SUN, Guoyun; LIU, Ying; SUN, Weixiang; WANG, Daoai (Frontiers of materials science, 2021)
Water-solid triboelectric nanogenerators (TENGs), as new energy collection devices, have attracted increasing attention in ocean energy harvesting and self-powered sensing. Polyacrylic acid (PAA) coating, usually used on the surface of marine equipment, has the property of anti-aging and anti-wear but limits triboelectrical output when used with TENGs. In this paper, polyacrylic acid coating was modified with fluorinated polyacrylate resin (F-PAA) to increase its triboelectrical output, by 6 times, and also to increase its anti-corrosion property. In addition, the corrosion resistance property can be further enhanced by cathodic protection using the electrical output generated by the water-flow triboelectrical energy transfer process. Given their easy fabrication, water-flow energy harvesting, and corrosion resistance, PAA/F-PAA coating-based TENGs have promising applications in river and ocean energy collection and corrosion protection.